Watering CanMEDS flowers - Voll, Sarah; Valiante, Taufik (Canadian Medical Education Journal, 2017)
We expand on the discourse related to nature surrounding Canadian medical training and the CanMEDS flower. We advance the notion that a major contributor to burnout is the increasing complexity and segregation of not only the medical profession, but society as a whole, leading to choice overload and an overemphasis on complex, data driven, rational decision making. We then propose that the key to watering CanMEDS flowers and preventing physician burnout lies in getting back to the basics of human behaviour.